Active regulation schemes to enhance the performance of thin film boiling using nanoporous membranes. (January 2022) - Li, Jiahua; Chen, Lin; Jin, Fengchu; Zhang, Yuannan; Wang, Qingyang; Xian, Haizhen; Lin, Jun
Highlights: Nanoporous membrane functions as both liquid distributor and heating substrate. Resistor network approach is extended to analyze the nanoporous membrane. Active regulation schemes are proposed for nanoporous membrane. Better manipulation and enhanced performance are achieved by regulation schemes. Abstract: With the help of the micro/nano-porous membranes, synergistic flows of supply water and departing vapor can be realized, which considerably enhances boiling heat transfer. Ultrahigh heat flux of 1230 W/cm 2 was reported in the thin film boiling experiments, of which the sample was fabricated by depositing nanosized platinum (Pt) layer on the surface of a nanoporous membrane. As an indispensable component, the nanoporous membrane plays an essential role by functioning as both the distributor of liquid fluid and the substrate of heating surface. However, there is still a lack of comprehensive understanding of the impacts of the nanoporous membrane. In this work, the resistor network approach developed in our former study was extended to analyze the influence of the nanoporous membrane on the performance of the unique thin film boiling. What's more, two active regulation schemes were proposed for nanoporous membrane to achieve better manipulation and enhanced performance. It was found that for a nonuniform nanoporous membrane, the critical heat flux was lower than that of a uniform membrane, and any further increase of electric power after reaching CHF would result in river-shaped crack of melted Pt resistors. For the nonuniform AAO membrane, the both active regulation schemes would effectively cope with the voltage fluctuation that could have led to the melt of the Pt layer. Therefore, better performance could be achieved by applying the active regulation schemes. Hopefully, the explorative studies on the active regulation schemes could provide operation guidance for future application of the thin film boiling.